Patient in the Physician's Perspective. Narrative Research - Beata Antoszewska (The Francis de Sales Scientific Society (TNFS.PL), 2022)
This theoretical and research paper focuses on the physician-patient relationship, and more specifically on the meanings ascribed to the notion of "patient". Authors of relevant literature indicate that particular models of the physician-patient relationship depend on the understanding of the notion of "patient" as well as on the understanding of two basic terms in medicine: health and illness. This assumption was the starting point for the presented analyses. Research was conducted within an interpretative paradigm framework. The study group consisted of physicians with different levels of experience and lengths of professional employment, as well as of various specializations. An analysis of collected data allowed for the identification of three categories of the notion of "patient": personal, subjective-objective and objective.